Determinants of risky sexual behaviour among young adults of South Africa - Zhou, Diana (My University, 2011)
Background Risky sexual behaviour, especially among 15-24 year olds, is a public health concern in South Africa since this age group is the most at risk of contracting HIV. The concern is to what extent youth are indulging in risky sexual behaviour. In 2002, the Department of Health conducted a nationally representative survey on issues surrounding HIV/AIDS. A mass media intervention was launched in the same year, i.e. the Khomanani Campaign, and a year later, in 2003, a survey was conducted to assess the impact of the Khomanani Campaign. Objectives The main question being asked is, “What are the factors associated with risky sexual behaviour amongst the young people of South Africa”. The indicators of risky sexual behaviour being explored are age of sexual debut, condom use at last sexual encounter, condom use in the past year and use of condoms consistently over the entire sexual lifetime. The three objectives of the research report are to describe the cohort of the youth in the sample under investigation, to describe the indicators of risky sexual behaviour among youth that are deemed at risk, and to investigate the factors associated with these indicators of risky sexual behaviour. Data The research uses the Khomanani Survey Findings of the Khomanani survey which was conducted in 2003, a year after the Khomanani Campaign. Only youth aged 15-24 years old who indicated that they were sexually active were included in the sample. Method The research is a cross sectional, secondary analysis of existing data, i.e. the Khomanani Survey Findings. Descriptive statistics were carried out and Chi-squares or Fisher’s exact tests were used for the initial bivariate analysis testing for associations between the indicators of risky sexual behaviour and the factors deemed to affect such behaviour. Factors such as media, self-esteem, self-efficacy, beliefs and accessibility of condoms which were deemed to be associated with risky sexual behaviours were explored in this report. Multiple logistic regression models were carried out with variables which were significant at p<0.20 in the bivariate analysis being included in the models. Factors that were significant in the multiple regression models were regarded as the most important variables to be associated with risky sexual behaviour. Results The final sample comprised 481 sexually active respondents with slightly more girls than boys (55% vs. 44% with 1% not indicating the gender); 48% of respondents were aged 15-19 years compared with 52% of respondents in the 20-24 age group. The majority of the youth had a partial secondary education. Only 5% of the youth were reported as married. The proportion of youth that had used a condom at last sexual encounter was 57%. The proportion of youth reporting that they used condoms consistently in the past year was 39% and some 28% of youth had used condoms consistently during the entire sex life. Of the 481 youth in the sample, 31% reported their first sexual encounter as before 16 years (“early sexual debut”). In the final regression model for condom use at last sex, females were 48% (aOR=0.52; 95% CI=0.34, 0.78) less likely to have used a condom at last sexual encounter compared with males. Being a youth from metropolitan areas was associated with condom use at the last sexual encounter (aOR=2.60; 95% CI=1.47, 4.57). Youth who have heard the term ‘safe sex’ were twice (aOR=1.98; 95% CI=1.10, 3.56) as likely to have used a condom at the last sexual encounter as to those who hadn’t heard the term “safe sex”. Being comfortable talking about using condoms with partners was also associated with use of condoms at last sex (aOR=3.86; 95% CI=1.74, 8.53). Concerns over the quality of government issued condoms were postulated to have an impact on condom use. Therefore respondents were asked whether they thought that government condoms differed from those purchased from shops. Respondents who indicated that condoms were the same were 2.71 times (aOR=2.71; 95% CI=2.28, 5.73) as likely to have used condoms consistently in the past year as those who indicated that government condoms were better than the ones from shops. Respondents who indicated that government condoms are of poor quality were 2.18 times (aOR=2.18; 95% CI=1.04, 4.58) as likely to have used condoms consistently in the past year as those who indicated that government condoms were better than the ones from the shops. Consistency in using condoms since being sexually active was associated with being from a metropolitan area (aOR=1.99; 95% CI=1.12, 3.51) and also respondents who had the opinion that condoms are the same (aOR=3.04; 95% CI=1.33, 7.07) whether they are government issued or from the shops.. The age of the respondent and also the belief that one should have sex with a partner to show their love were the only factors associated with early sexual debut. Respondents who were older (20-24 years) were 61 %( OR=0.39; 95% CI=0.23, 0.65) less likely to have had early sexual debut below the age of 16 compared to their counterparts aged 15-19 years. Respondents who did not believe that a person should have sex with their partner to show their love were 41 %( OR=0.59;95% CI=0.37,0.94) less likely to have had early sexual debut to those who believed that a person should have sex with their partner to show their love controlling for gender, area of stay, age group and employment. Conclusions The findings from the survey point out that more than half of the youth are using condoms at most recent activities, with differences between men and women. Some youth are consistently using condoms and not only using at last sex. Hence programs targeting youth should continue taking into account issues that may be contributing to youth not using condoms and not using them consistently. Messages on safe sex, messages encouraging youth to communicate with partners on sexuality issues, as well as the government making condoms accessible in all areas, should continue to be reinforced. Future research should also focus on development and evaluation of interventions to delay sexual debut with issues of beliefs, and community beliefs being discussed.
Keywords: Sexual Behavior--adolescent; HIV Infections|xprevention & control|xadolescent